METAPHORS IN BRING ME THE HORIZONS SELECTED SONG LYRICS - Laurentius Jalu Waskitho Jati (UC Journal: ELT, Linguistics and Literature Journal, 2020)
This research aims to analyze the selected Bring Me The Horizons song lyrics. There are two selected songs entitled Drown and Throne. The songs were chosen based on the variety of words used in the song lyrics. The aim of this research is to find out the types of metaphors found and the meanings of the selected songs. As a result, there are two research questions, namely: First, what types of metaphors are found in Bring Me The Horizon?s selected song lyrics? Second, what are the meanings of the songs? There are two sources that are used in this research. They are the primary subject and the secondary subject. The primary subject is two selected Bring Me The Horizons song lyrics. The secondary subjects are theories and information about metaphors, denotative and connotative meaning, formalist approach and biographical approach. The researcher used theories about metaphors and formalist approach in answering the first research question, while the theories about denotative and connotative meaning and biographical approach are used to answer the second research question. The researcher found three types of metaphors are used in Bring Me The Horizon?s selected song lyrics, namely: conventional metaphor, mixed metaphors and new metaphor. Conventional metaphor is the type of metaphor that mostly used in the selected song lyrics. After the types of metaphors are found, the researcher analyzes the meanings of the songs. Drown song tells about a person who is lonely, depressed and frustrated. Throne song tells about a person who wants to prove to others that he can do more than what people think.